Plastic occurrence in six different species of Arctic seabirds - Harmonizing methods and closing knowledge gaps on plastic occurrence and polymer identity - Benjaminsen, Stine Charlotte (UiT Norges arktiske universitet, 2021)
The once pristine Arctic is now facing negative alterations with a rapidly changing climate, increasing human activity, and plastic pollution. Seabirds are intrinsic to the marine ecosystems, and in recent years, plastic ingestion by seabirds has been of increasing concern because of the potential negative impact on individual and population levels. The aim of this study was to investigate the plastic occurrence and characterize the polymer identity of plastics found in six seabird species breeding in the Arctic. The study species were Atlantic puffins (Fratercula arctica), Common guillemots (Uria aalge), Razorbills (Alca torda), Great cormorants (Phalacrocorax carbo), European shags (Phalacrocorax aristotelis), and Glaucous gulls (Larus hyperboreus). We showed that the Atlantic puffins had a high frequency of occurrence of plastic and proved plastic ingestion for the first time in Glaucous gulls. No plastic was detected in the Common guillemots, Razorbills, Great cormorants, and European shags. Non-invasive methods to detect and measure plastic in seabirds should be further investigated, and research on the toxic effects from plastic exposure should be intensified. The study has proven to be valuable by providing new quantitative and qualitative data on plastic loading and polymer type reported in a standardized manner which can be used to establish a baseline for future research and monitoring of Arctic seabirds on a national and international level. Arctic, Seabirds, Atlantic puffin, Common guillemot, Razorbill, Great cormorant, European shag, Glaucous gull, Plastic, Plastic pollution, Plastic ingestion, Polymer profile, Polymer identification, FTIR